Pengawasan Dinas Lingkungan Hidup terhadap Pembuangan Sisa Limbah Industri Rumah Binatu - Sang Kompiang Kurnia Yudha Putra; I Wayan Arthanaya; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2020)
Indonesia is well-known as a developing country being rich in tourist objects and its people who have been opening many businesses to earn more income. One of the businesses that are interrelated with the world of tourism is a laundry house service, engaged in laundry services, which makes this business attractive to a lot of residents and whose services are often used by tourism places. The laundry house industry is growing rapidly along with the increasing activity of residents. In this regard, this study examines two issues: (1) the supervision of the Environmental Agency on the laundry house industry in the disposal of waste residue and (2) the application of sanctions against perpetrators of violations of waste disposal as seen from the Regional Regulation of the City of Denpasar Number 11 of 2015. The method use to achieve these objectives is the method of empirical legal research which is carried out by conducting research examining the arising problems based on legal rules and then related to the realities in the field. The Environmental Agency of Denpasar City has enforced control of the breaking pf rules that have occurred; if there is a laundry house that violates it, a written statement is be issued but if the laundry house does not repair the waste treatment system, a warning letter is be issued. Ultimately, if the violation continues to take place, decisive repression in light criminal act is executed in collaboration with the local civil service police unit.